ω-3 DPA Protected Neurons from Neuroinflammation by Balancing Microglia M1/M2 Polarizations through Inhibiting NF-κB/MAPK p38 Signaling and Activating Neuron-BDNF-PI3K/AKT Pathways - Baiping Liu; Yongping Zhang; Zhiyou Yang; Meijun Liu; Cai Zhang; Yun‐Tao Zhao; Cai Song (2021)
Microglia M1 phenotype causes HPA axis hyperactivity, neurotransmitter dysfunction, and production of proinflammatory mediators and oxidants, which may contribute to the etiology of depression and neurodegenerative diseases. Eicosapentaenoic acid (EPA) may counteract neuroinflammation by increasing n-3 docosapentaenoic acid (DPA). However, the cellular and molecular mechanisms of DPA, as well as whether it can exert antineuroinflammatory and neuroprotective effects, are unknown. The present study first evaluated DPA's antineuroinflammatory effects in lipopolysaccharide (LPS)-activated BV2 microglia. The results showed that 50 μM DPA significantly decreased BV2 cell viability after 100 ng/mL LPS stimulation, which was associated with significant downregulation of microglia M1 phenotype markers and proinflammatory cytokines but upregulation of M2 markers and anti-inflammatory cytokine. Then, DPA inhibited the activation of mitogen-activated protein kinase (MAPK) p38 and nuclear factor-κB (NF-κB) p65 pathways, which results were similar to the effects of NF-κB inhibitor, a positive control. Second, BV2 cell supernatant was cultured with differentiated SH-SY5Y neurons. The results showed that the supernatant from LPS-activated BV2 cells significantly decreased SH-SY5Y cell viability and brain-derived neurotrophic factor (BDNF), TrkB, p-AKT, and PI3K expression, which were significantly reversed by DPA pretreatment. Furthermore, DPA neuroprotection was abrogated by BDNF-SiRNA. Therefore, n-3 DPA may protect neurons from neuroinflammation-induced damage by balancing microglia M1 and M2 polarizations, inhibiting microglia-NF-κB and MAPK p38 while activating neuron-BDNF/TrkB-PI3K/AKT pathways.